The Derrida-Habermas reader - Thomassen, Lasse (Edinburgh University Press, 2006)
This work considers the debate between two of the most prominent philosophers and social theorists of the 20th century: Jacques Derrida and Jürgen Habermas. It presents a collection of articles by the two figures and by those who have written about them, and includes pieces published in English for the first time.